HUBUNGAN TINGKAT PENGETAHUAN HYGIENE DENGAN KEBERADAAN Escherichia coli PADA JAMU TRADISIONAL (BERAS KENCUR) DI MANGKANG SEMARANG - Purnomo Purnomo; Tri Joko; Niki Astorina Yunita Dewanti (Jurnal Kesehatan Masyarakat (Undip), 2016)
Traditional herbal medicine is one product of home industry, the manufacturing process is often less attention to sanitation and Higiene. Behavior seller and manufacturer of traditional herbal medicine in treating herbal medicine is still less attention to hygiene factors, as the indicator is still the existence of microbial contamination in carrying medicinal. Detection Escherichiacoli in carrying medicinal in 10 (ten) market in Semarang stated that of the 40 (forty) samples carrying medicinal examined 22 (twenty two) samples contaminated with bacteria Escherichia coli, four (4) samples are not contaminated and 14 (fourteen) samples were contaminated with bacteria. To study was to analyze the correlation between knowledge of hygiene and identification of the presence of Escherichia coli, describing the characteristics of the respondent, processing, quality of water, personal hygiene, hygiene knowledge level, identification of Escherichia coli in traditional herbal rice kencur. The method used is observational with cross sectional approach. The results obtained from 20 respondents obtained a good knowledge level results 12 (60%), lack of knowledge 8 (40%), the presence of Escherichia coli positive 8 (40%), negative 12 (60%). The level of knowledge badly contaminated with Escherichia coli as much as 6 samples, while the level of knowledge of both the contaminated Escherichia coli 2 samples. The results of the statistical test using chi square p value of 0.009 means that there is a correlation between the level of hygiene knowledge of traditional herbalist with the presence of Escherichia coli in herbal rice kencur.In conclusion the level of knowledge of good hygiene as many as 12 people (60%), lack of knowledge level of 8 people (40%). A total of 40% of traditional herbal rice kencur experience microbes Escherichia coli contamination. There is a relationship with the level of hygiene knowledge of the existence of Escherichia coli in herbal rice kencur (p value = 0.009)